Самоорганізовна інкрементна нейронна мережа для кластерування масивів даних - Іванова, Є. В. (My University, 2018)
In the paper self-organizing incremental neural network for multidimensional data sets. It is proposed to accomplish the task of clustering and represent the topological structure of the input data. Self-organizing incremental neural network find typical prototypes for large-scale data set and robust to noise.
Keywords: нейронна мережа; incremental neural network